ANALISIS BEBAN KERJA FISIK OPERATOR PADA BAGIAN PROSES PRODUKSI AIR MINUM DALAM KEMASAN DENGAN MENGGUNAKAN PENDEKATAN FISIOLOGIS PADA INDUSTRI AIR MINUM DALAM KEMASAN - Saputra, Rinaldi; Maryam, Maryam (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2020)
One of the industries operating in the field of bottled drinking water (AMDK) in West Sumatra, in its production process, involves many workers or production operators, including water filling, packaging and lifting. Through interviews with several workers, it was found that the work of filling water, packing and lifting is quite heavy compared to other jobs. In order to measure the operator's physical workload, two methods will be used objectively, namely the direct method and the indirect method, as well as using the Nordic Body Map (NBM) questionnaire to determine disease complaints. After measuring, the results of the study show that the average value of Energy Expenditure for morning work is 8.65 kcal/minute (heavy workload) and for evening work is 11.74 kcal/minute (very heavy workload). The average value of energy consumption is 3.92 kcal/minute and has not exceeded the standard energy consumption limit for men which is 5 kcal/minute. In calculating the CVL percentage of operators, the average CVL percentage was found to be 41.69%, which means that the working conditions need to be improved. Based on the NBM questionnaire, it was concluded that the highest complaints were in the left shoulder, right shoulder, left arm, right arm, left calf, right calf, left leg and right leg, which are parts directly related to the operator's working position.